The role of the project resource planning system in strengthening the strategic planning process - Ibrahim , hakeem khalill; Salih, Mohammed Abed; Ibraheem, Muthanna Firas (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the research is to define the role and impact of the ERP system (communication, selection of systems package, support to senior management, training, organization management for application) in the strategic planning process (strategic vision, mission, strategic goals, strategic analysis, strategic choice) in an oil company The North through a field study and the diversity of their administrative levels. The research has been applied to the sample consisting of (83) people from different departments in the organization by relying on the questionnaire as a main tool for collecting data and information. ERP Enhancing the strategic planning process in the researched organization as well as having a significant impact relationship between the ERP system ERP Enhancing the strategic planning process in the researched organization, so the research recommends the need to adopt the two themes of the ERP system in strengthening the strategic planning process as a dominant culture in the manufacturing process being Long-term profitable source.